2005
DOI: 10.1007/s11135-005-8105-4
|View full text |Cite
|
Sign up to set email alerts
|

On estimating the proportion of a qualitative sensitive character using randomized response sampling

Abstract: In this paper, we present results pertaining to investigations concerning randomized response sampling. We consider a simple generalization for some existing investigations, and then provide the suitable choices for design parameters. It is also demonstrated the superiority of the proposed procedure over Warner (1965) procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The RR procedure proposed by Chang et al (2004) has one RD which consists of four statements: "I belong to group A", "I do not belong to group A", 'Yes', 'No', with probabilities p CH 1 , p CH 2 , p CH 3 and p CH 4 ( 4 i=1 p CH i = 1), respectively. When p CH 3 = 0 and p CH 4 = 1 − p CH 1 − p CH 2 , the above model reduces to the model.…”
Section: The Chang Et Al (2004) Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The RR procedure proposed by Chang et al (2004) has one RD which consists of four statements: "I belong to group A", "I do not belong to group A", 'Yes', 'No', with probabilities p CH 1 , p CH 2 , p CH 3 and p CH 4 ( 4 i=1 p CH i = 1), respectively. When p CH 3 = 0 and p CH 4 = 1 − p CH 1 − p CH 2 , the above model reduces to the model.…”
Section: The Chang Et Al (2004) Modelmentioning
confidence: 99%
“…When p CH 4 = 0 and p CH 3 = 1 − p CH 1 − p CH 2 , the model reduces to the Bhargava and Singh (2000) model. The L-level of PP of the Chang et al (2004)…”
Section: The Chang Et Al (2004) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the probability T is unknown in actual practice. To overcome such a difficulty, Chang and Huang (2001), Huang (2004), and Chang et al (2004a) have suggested alternative survey strategies which make it possible to estimate the unknown parameters π and T simultaneously. Two alternatives to Huang's (2004) randomized response model, based on Singh (1993) models, are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent exposition of modifications on RR techniques and other related works could be referred to Chaudhuri and Mukerjee [6]. Some resent developments are Bhargava and Singh [1], Chua and Tsui [7], Padmawar and Vijayan [12], Singh et al [14], Chang and Huang [2], Chaudhuri [5], Singh et al [13], Huang [10], and Chang et al [3,4], etc. In particular, to quantify the sensitivity level for certain items of inquiry in practice, Gupta et al [9] first shown how an estimator may be developed on the quantitative characteristics.…”
Section: Introductionmentioning
confidence: 99%